Comparative Study between Clinical and Sonographic Estimation of Fetal Weight in Third Trimester of Pregnancy and Its Relationship with Actual Birth Weight - Nahar, N; Akhter, N; Hoque, ME; Ferdous, S; Mustafa, MR (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):157-63. The abstract of this article is available on the PubMed website